A rare case of a systemic-to-pulmonary veno-venous connection: a pause during development of pulmonary and systemic venous separation. (6th February 2017) - Kwak, Jae Gun; Kim, Kyung-Hee; Lee, Chang-Ha
Abstract: A 45-year-old man with dyspnoea and palpitations exhibited a unique systemic-to-pulmonary veno-venous connection on preoperative CT images. A window of 31.5-mm diameter was evident between the superior caval vein and the middle pulmonary vein, which was normally connected to the left atrium via a 30-mm-diameter orifice. The atrial septum was intact.